Culturing Layer-Specific Neocortical Neurons as a Cell Replacement Therapy Following Traumatic Brain Injury - Cramer, Nathan P.; Chatterjee, Mitali; Lischka, Fritz; Juliano, Sharon L. (Frontiers in Neurology, 2014)
Neurophysiological changes resulting from traumatic brain injury (TBI) can result in adverse changes in behavior including mood instability and cognitive dysfunction. Cell death following TBI likely contributes to these altered behaviors and remains an elusive but attractive target for therapies aiming at functional recovery. Previously we demonstrated that neural progenitor cells derived from embryonic rats can be transplanted into donor neonatal rat brain slices and, over the course of two weeks in culture, mature into neurons that express neuronal immunohistochemical markers and develop electrophysiological profiles consistent with excitatory and inhibitory interneurons. Here we examine the potential of generating electrophysiologically mature neurons with a layer-specific phenotype as a next step in developing a therapy designed to rebuild a damaged cortical column with the functionally appropriate neuronal subtypes. Preliminary results suggest that neurons derived from passaged neurospheres and grown in dissociated cell culture develop GABAergic and presumed glutamatergic phenotypes and that the percentage of GABAergic cells increases as a function of passage. After two weeks in culture, the neurons have a mix of immature and mature neuronal electrophysiological profiles and receive synaptic inputs from surrounding neurons. Subsets of cells expressing neuron specific markers also express layer specific markers such as Cux1, ER81, and RORβ. Future studies will investigate the potential of transplanting layer specific neurons generated and isolated in vitro into the neocortex of neonatal brain slices and their potential to maintain their phenotype and integrate into the host tissue.